The psychology of learning and motivation. - Federmeier, Kara D. (Psychology of learning and motivation, 2019)
The Psychology of Learning and Motivation, Volume 71 , the latest release in the series, features empirical and theoretical contributions in cognitive and experimental psychology, ranging from classical and instrumental conditioning to complex learning and problem-solving. New to this volume are chapters covering Automating adaptive control with item-specific learning, Cognition and voting: Generalizing from the laboratory to the real-world voting booth, Protracted perceptual development of auditory pattern structure, Understanding alcohol reward in social context, Perceptual and Mnemonic Differences across Cultures, Aging, Cognitive Reserve and the Healthy Brain, Aging, context processing, and comprehension, and more. Presents the latest information in the highly regarded Psychology of Learning and Motivation series Provides an essential reference for researchers and academics in cognitive science Contains information relevant to both applied concerns and basic research.